The role of fertilizer in transforming agriculture in Asia: A case study of the Indian fertilizer sector - Sharma, Vijay Paul (International Food Policy Research Institute, 2014)
The role of chemical fertilizers for increased agricultural production, particularly in developing countries such as India, is well estab-lished. Some argue that fertilizer was as important as seed in the Green Revolution (Tomich et. al. 1995), contributing as much as 50 percent to the yield growth in Asia (Hopper 1993, FAO 1998). Others have found that one-third of worldwide cereal production is due to the use of fertilizer and related factors of production (Bumb 1995).